2017
DOI: 10.1080/15299732.2017.1329771
|View full text |Cite
|
Sign up to set email alerts
|

The role of evidence-based therapy relationships on treatment outcome for adults with trauma: A systematic review

Abstract: More research is needed on the roles of client feedback, managing countertransference, and other therapist characteristics on treatment outcome with trauma survivors. Understanding the role of EBRs in the treatment of trauma survivors may assist researchers, clinicians, and psychotherapy educators to improve therapist training as well as client engagement and retention in treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…Higher working alliance at the start of treatment, as rated by both patients and therapists after session 1, was associated with greater symptom improvement, measured by symptom scores at the end of treatment, controlled for baseline scores. This extends the earlier findings of Brady et al (18), who found that patients reporting a stronger working alliance were more likely to respond well to CT-PTSD, and replicates the findings of numerous other studies which have found a positive association between working alliance and therapy outcome, including in PTSD treatment (15). Although the effect sizes in our study were of small to medium size, they are in line with those of other studies in a range of different disorders (1,3,15).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Higher working alliance at the start of treatment, as rated by both patients and therapists after session 1, was associated with greater symptom improvement, measured by symptom scores at the end of treatment, controlled for baseline scores. This extends the earlier findings of Brady et al (18), who found that patients reporting a stronger working alliance were more likely to respond well to CT-PTSD, and replicates the findings of numerous other studies which have found a positive association between working alliance and therapy outcome, including in PTSD treatment (15). Although the effect sizes in our study were of small to medium size, they are in line with those of other studies in a range of different disorders (1,3,15).…”
Section: Discussionsupporting
confidence: 92%
“…This extends the earlier findings of Brady et al (18), who found that patients reporting a stronger working alliance were more likely to respond well to CT-PTSD, and replicates the findings of numerous other studies which have found a positive association between working alliance and therapy outcome, including in PTSD treatment (15). Although the effect sizes in our study were of small to medium size, they are in line with those of other studies in a range of different disorders (1,3,15). These results support the importance of establishing a good working relationship with patients in trauma-focused psychological therapies for PTSD, which is associated with treatment outcomes, although other processes such as reduction of negative appraisals also play a role (43).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The therapeutic relationship has been conceptualised and investigated across a broad range of therapeutic approaches and contexts (Orlinsky et al, 2004). Empirically, the quality of the therapeutic relationship has been positively associated with treatment outcomes across a range of therapeutic styles, presenting problems and treatment settings, including (Barnao, Ward, & Casey, 2016;Ellis, Simiola, Brown, Courtois, & Cook, 2017;Hewitt & Coffey, 2005;Horvath, Re, Flückiger, & Symonds, 2011;Meier et al, 2005) improved outcomes for domestic violence treatment (Taft & Murphy, 2007), sexual offending treatment (Beech & Hamilton-Giachritsis, 2005) and the prison population (Huffman, 2013). Given that there is a general consensus that the therapeutic relationship plays a crucial role in treatment outcomes across the psychological and counselling literatures, it is curious then, that it has received such little theoretical and empirical attention in the field of forensic treatment.…”
Section: Therapeutic Relationshipmentioning
confidence: 99%